Elevated β-Carotene Production Using Codon-Adapted CarRA&B and Metabolic Balance in Engineered Yarrowia lipolytica - Liu, Liang; Qu, Yu Ling; Dong, Gui Ru; Wang, Jing; Hu, Ching Yuan; Meng, Yong Hong (Frontiers in Microbiology, 2021)
β-carotene is a precursor of vitamin A and has multiple physiological functions. Producing β-carotene by microbial fermentation has attracted much attention to consumers’ preference for natural products. This study focused on improving β-carotene production by constructing codon-adapted genes and minimizing intermediate accumulation. The codon-adapted CarRA and CarB genes from the industrial strain of Blakeslea trispora were integrated into the genome of the Y. lipolytica to construct YL-C0, the baseline strain for producing β-carotene. Thereafter, the β-carotene biosynthetic pathway’s metabolic balance was accurately regulated to reduce the intermediates’ accumulation. Notably, the β-carotene content increased by 21 times to reach 12.5 dry cell weight (DCW) mg/g when minimizing HMG-CoA and FPP accumulation. Further, we improved the expression levels of the CarRA and CarB genes to minimize the accumulation of phytoene and lycopene. Total production of β-carotene of 1.7 g/L and 21.6 mg/g DCW was achieved. These results reveal that the rate-limiting enzymes CarRA and CarB of B. trispora exhibited higher catalytic activity than the same enzymes from other microorganisms. Promoting metabolic balance by minimizing the accumulation of intermediates is a very effective strategy for increasing β-carotene. The β-carotene-producing strain constructed in this study has established the foundation for its potential use in industrial production. These successful engineering strategies also provide a foundation for large-scale production of other terpenoids.